Eating behaviour analysis and its psychological factors in non-obese university population - López Morales, José Luis (Anales de Psicología / Annals of Psychology, 2017)
The eating beahaviour of obese population can be influenced by various psychological factors such us eating restriction, lack of control or emotional eating. Although in most ocassions this variables have been studied in obese population, the aim of this study is to evaluate the relations between this factors with eating behaviour in non-obese population and relate this behaviour with Edorexia Syndrome. A battery of psychological tests was applied to 75 students of Murcia University, this battery consisted of the Edorexia Syndrome Questionnaire, Big Five Personality Questionnaire and the Coping Response Inventory (CRI-A). The results showed how the Edorexia Syndrome was related with a dicrease in emotional stability, emotional control and positive reevaluation as well as an increase in acceptance and resignation. In addition, people with Edorexia Syndrome were related to dieting, food deprivation, exercising and consumption without needing. This results are explained by the Five Ways Theory (Macht, 2008) which relates the lack of skills to cope with emotions with the uncontrollable abuse of food.